Monetary policy and potential output uncertainty: a quantitative assessment - Simona Delle Chiaie (European Central Bank (ECB), 2009)
I estimate a dynamic stochastic general equilibrium model where the policymaker and the private sector have imperfect knowledge about potential output. The estimation of the structural parameters and of the monetary authorities'objectives is key to assess the quantitative relevance of the imperfect information problem and to evaluate the robustness of previous exercises based on calibration. The estimated model also allows me to revisit the Orphanides (2001, 2003) findings that the central bank can makes large and persistent mistakes to estimate potential output in response to productivity and cost shocks. I find that when real unit labor cost is used as a monetary policy indicator, the potential output uncertainty has quantitatively negligible consequences on policy behaviour and inflation dynamics.
Keywords: E4; E5; 330; indicator variables; monetary policy; potential output uncertainty; real unit labor cost; Geldpolitik; Produktionspotenzial; Unvollkommene Information; Monetärer Indikator; Lohnstückkosten; Theorie